Towards an understanding of mental touchness in Australian Football - Gucciardi, Daniel; Gordon, S.; Dimmock, J. (Routledge, 2008)
A personal construct psychology (PCP; Kelly, 1955/1991) framework was employed in anattempt to reveal a holistic understanding of mental toughness in the context of AustralianFootball. Eleven male coaches (M age = 42, SD = 9.62) with considerable playing andcoaching experience at the elite level were interviewed using a PCP-based interview protocol.Transcribed verbatim datawere analyzed using grounded theory procedures. Three independentcategories (characteristics, situations, behaviors) were inductively derived and integrated into amodel inwhich the importance of understanding each component individuallywas emphasized.The relationship between these three central categories was also highlighted. Results identifiedthe key mental characteristics and their contrasts together with those situations that demandmental toughness, and the behaviors commonly displayed by mentally tough footballers.Conceptualized in the context of these three categories, mental toughness in Australian Footballcan be considered as a buffer against adversity but also as a collection of enabling factors thatpromote and maintain adaptation to other challenging situations. Practical implications of thefindings are discussed and focus on issues pertaining to enhancing and/or developing mentaltoughness.